Effect of Bekang, Naturally Fermented Soyabean Food, as Alternative to Antibiotic Growth Promoter on Feed Efficiency, Blood Biochemical and Gut Health Parameters of Broiler Birds - Buragohain, Rajat; Das, Suraj (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during the month of October-November, 2021 to assess effect of Bekang, naturally fermented soyabean food of Mizoram, on feed efficiency and gut health parameters of broilers as alternative to AGP. Total 240 day-old Vencobb-400 broiler chicks were assigned six dietary treatments dividing into six homogenous groups - standard rations (T1), standard rations with AGP (Bacitracin Methylene Disalicylate) @ 0.5 g kg-1 (T2), standard ration with fermented feed by Lactobacillus acidophilus (106–108 CFU g-1) @ 100 g kg-1 (T3), and standard rations with Bekang @ 50 g kg-1 (T4), 75 g kg-1 (T5) and 100 g kg-1 (T6), respectively. Findings revealed significant effect of Bekang on body weight gain at 42nd day of age, feed conversion ratio and economic return score of broilers. No significant effect was observed on blood biochemical parameters. Histomorphological studies revealed significantly (p<0.05) increased villi length, width, and decreased crypt depth in all prats of small intestine for Bekang supplementation. Caecal bacterial counts revealed increasing trend of lactic acid bacteria and decreased Salmonella and E. coli counts in T4, T5 and T6 compared to T1, T2 and T3. An increasing trend of antibody titre against NDV on 35th day of age indicated improvement of immune status in Bekang supplemented birds. From the findings, it was concluded that Bekang could be a potential alternative to AGP and could be recommended at a level of 50 g to 100 g kg-1 in rations of broiler birds.